PENERAPAN TEKNIK LAYANAN KONSELING PERORANGAN OLEH GURU BK DALAM MEMBENTUK KARAKTER DISIPLIN PESERTA DIDIK - Citra Imelda Usman (Jurnal Counseling Care, 2017)
The background of this research is the existence of some students who display undisciplinedbehavior in school, such as coming late to come to school and so forth. The purpose of this studyis how the effectiveness pelaysanaan individual counseling services in mendisipnlikan class Xstudents electrical majors in SMK Negeri 5 Padang, using general and special techniques. Theresearch is quantitative descriptive research. The population of this study were 38 students ofclass X of electrical majors at SMK Negeri 5 Padang who had attended individual counseling. Thesampling technique is total sampling. The instrument used is a questionnaire. Data analysistechnique used is technique percentage. The findings of this study indicate that: 1) theapplication of general and specialized techniques to individual counseling can improve studentdiscipline. This research is recommended for students of electric X class X who have participatedin individual counseling services to improve their discipline. Then to the school community, inorder to give full attention to the students and to cooperate with all the personnel or citizens ofschool which aims in improving the discipline of learners.Keywords: General techniques of individual counseling services, specific techniques ofindividual counseling services, discipline